Responsive, Integrity, Morality and Fairness Law Enforcement as Social Change Instrument - Nur, Fuad; Zulfadli, Muhammad; Arifin, Gunawan; Abdullah, Kasman; Salle, Aminuddin (Faculty of Law Cenderawasih University, 2016)
This article reviews the essence of law enforcement as social change instrument. Law in the context of Indonesia that embrace democratic system is upholding the justice values in it that fairness principles for all Indonesian people. As positive law in a legal state, law enforcement is required to be professional, proportional, good, fair, and wisely so in accordance with the rules of expediency, kindness and equality in the law itself. The outcomes of the research indicate that law and community cannot be separated, for law the community is a resource that gives life (to nature) and move the law. The communities live the law with the values, ideas, concepts. And also contribute the community to implement the law.